2013
DOI: 10.1371/journal.pone.0072386
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cadherin-17 Antibody Modulates Beta-Catenin Signaling and Tumorigenicity of Hepatocellular Carcinoma

Abstract: Cadherin-17 (CDH17) is an oncofetal molecule associated with poor prognostic outcomes of hepatocellular carcinoma (HCC), for which the treatment options are very limited. The present study investigates the therapeutic potential of a monoclonal antibody (Lic5) that targets the CDH17 antigen in HCC. In vitro experiments showed Lic5 could markedly reduce CDH17 expression in a dose-dependent manner, suppress β-catenin signaling, and induce cleavages of apoptotic enzymes caspase-8 and -9 in HCC cells. Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
(50 reference statements)
0
24
1
Order By: Relevance
“…Previous study has shown that CDH17 could be a biomarker for gastric carcinoma and attractive therapeutic target for this aggressive malignancy (18). Recent reports also demonstrated that the expression of CDH17 in HCC was associated with vascular invasion, tumor metastasis, advanced tumor stage, and poor prognosis (12,13,19,20). The therapeutic significance was determined as well that, by targeting CDH17, we can inhibit tumor growth in HCC (13,19).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous study has shown that CDH17 could be a biomarker for gastric carcinoma and attractive therapeutic target for this aggressive malignancy (18). Recent reports also demonstrated that the expression of CDH17 in HCC was associated with vascular invasion, tumor metastasis, advanced tumor stage, and poor prognosis (12,13,19,20). The therapeutic significance was determined as well that, by targeting CDH17, we can inhibit tumor growth in HCC (13,19).…”
Section: Discussionmentioning
confidence: 97%
“…Given substantial correlation between CK19 and CDH17 expressions, we believe that the high recurrence rate and poor prognosis of CK19(+) HCC may be attributed to CDH17 expression. Since CDH17 has been reported to influence HCC outcome by targeting Wnt/β-catenin pathway, anti-CDH17 Ab or inhibitors of Wnt/β-catenin pathway may have promising effects for CK19(+) HCC (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor formation was studied by establishing a mouse xenograft model as described previously. 17,30 Lentiviral vectors (Shanghai JRDUN Biotechnology Co., Ltd) expressing miR-622 (LV-miR-622) or control miRNA were used to infect MHHC-97H cells according to the manufacturer's instructions. BALB/c female nude mice (4 weeks old) were purchased from Experimental Animal Center of Shanghai, Shanghai, China.…”
Section: Tumorigenicity In Nude Micementioning
confidence: 99%
“…Fontenot et al (151) reported in their recent research that SFRP2 monoclonal antibody could induce the antitumor effect and inhibit the Wnt/β-catenin signaling pathway in breast models. Wang and colleagues also found a dose-dependent effect of anti-cadherin-17 antibody in suppressing β-catenin in a HCC model (152). Similarly, Gao et al (153) reported that HS20, a human monoclonal (149) antibody against glypican-3, could disrupt the stability of Wnt3a and glypican-3 and inhibit the Wnt/β-catenin signaling pathway in HCC cells.…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 90%